True or False?
Let S ⇒ 2 1 S = 1 1 − 2 1 + 3 1 − 4 1 + 5 1 − 6 1 + ⋯ = 2 1 − 4 1 + 6 1 − 8 1 + ⋯ . Adding the two equations and regrouping gives 2 3 S ⇒ S = ( 1 1 + 3 1 + 5 1 + ⋯ ) − 2 ( 4 1 + 8 1 + 1 2 1 + ⋯ ) = 1 1 − 2 1 + 3 1 − 4 1 + ⋯ = S = 0 . Therefore, 1 1 − 2 1 + 3 1 − 4 1 + ⋯ = 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( 1 1 − 2 1 ) + ( 3 1 − 4 1 ) + ⋯ + ( n 1 − ( n + 1 ) 1 ) + ⋯
is a series of positive terms. It cannot, therefore, add up to a zero.
This series can be written as a n = n ( − 1 ) n . It converges: we can see that for example applying Leibniz's rule. However, the statement is wrong because this series is not absolutely convergent: ∣ a n ∣ = n 1 diverges - I know, it's counter-intuitive, but it does. And there is a beautiful theorem (Riemann's theorem) which states that if you have a series that is convergent but not absolutely convergent, if you want to rearrange the terms (it's called a permutation), you can make them have any sum you like.
Problem Loading...
Note Loading...
Set Loading...
The series is not absolutely convergent so rearranging it may change the value of the sum.